logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

Choose the correct answer. The statement $p \rightarrow (q \rightarrow p)$ is equivalent to which of the following?

$\begin{array}{1 1} (A) p \rightarrow (p \rightarrow q) \\(B) p \rightarrow (p \vee q) \\ (C) p \rightarrow (p \wedge q) \\ (D) p \leftrightarrow (p \rightarrow q)\end{array}$

Can you answer this question?
 
 

1 Answer

0 votes
$p \rightarrow (q \rightarrow p) \equiv \sim p \vee (q \rightarrow p)$ $\equiv \sim p \vee (\sim q \vee p)$
$\qquad \equiv \sim q \vee (p \vee \sim p ) \equiv \sim q \vee T = T$
$\Rightarrow p \rightarrow (q \rightarrow p) $ is a tautology.
Also, $p \rightarrow (p\vee q) \equiv \sim p \vee (p \vee q ) \equiv (~p \vee p) \vee q \equiv T \vee q \equiv T$
$\Rightarrow p \rightarrow (p \vee q ) $ is also a tautology.
$\Rightarrow p \rightarrow (q \rightarrow p) \equiv p \rightarrow (p \vee q ) $
answered Mar 20, 2014 by balaji.thirumalai
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...